Analysis of the Effect of SEO and Social Media Marketing on Course Package Purchase Decisions Through Purchase Interest as an Intervening Variable at LKP Yale Communication - Ferianto, Ferianto; Setiawan, Joko; Hermawan, Hermawan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the effect of Search Engine Optimization (SEO) and Social Media Marketing on the decision to purchase course packages through purchase interest as an intervening variable at LKP Yale Communication. The main focus is to identify how these two digital marketing approaches influence purchasing decisions and the extent to which purchase interest acts as a mediator in the process. Methodology: This study uses a quantitative approach, with data collected through questionnaires distributed to 185 respondents. The variables studied include SEO, Social Media Marketing, Purchase Interest, and Purchase Decisions. Data analysis was performed using the Partial Least Squares (PLS) method to measure the relationship between these variables and to see the direct and indirect effects. Results: The results of the analysis show that: SEO has a significant direct effect on Purchase Interest and Purchase Decision. Social Media Marketing has a significant effect on Purchase Interest, but does not show a direct effect on Purchase Decision. Purchase Intention serves as a significant mediating variable in the relationship between SEO and Social Media Marketing on Purchase Decision. Findings: This study found that: SEO strategies are more effective in directly influencing purchase decisions than Social Media Marketing. Social Media Marketing plays an important role in generating purchase intention, which in turn influences purchase decisions. Purchase intention is a key element in linking the impact of SEO and Social Media Marketing on Purchase Decisions. Novelty: The innovation of this study lies in combining SEO and Social Media Marketing in a single analytical framework that considers the role of purchase intention as an intervening variable. This provides new insights into how both digital marketing strategies can be effectively utilized in the context of non-formal education. Originality: Although many previous studies have explored SEO and Social Media Marketing separately, this study offers a new perspective by combining these two elements and making purchase interest a mediator. This study also enriches the literature in the non-formal education sector, which is often under-researched by academics. Conclusion: The conclusion of this study shows that integrated digital marketing strategies are very important for increasing purchasing decisions in the non-formal education sector. The results of the study emphasize the need for greater attention to SEO as an effective tool to directly influence purchasing decisions, while Social Media Marketing should be seen as a means to develop consumer purchase interest. This study is expected to contribute to the development of digital marketing strategies and serve as a reference for further research in this field. Type of Paper: research article